The Utilization of Process Evaluations in Childhood Obesity Intervention Research: A Review of Reviews - Branscum, Paul; Hayes, Logan (International Journal of Child Health and Nutrition, 2013)
Process evaluations are an essential component to evaluating health promotion programs, however they are consistently under-utilized and oftentimes not reported upon in the literature. This study reports the use of process evaluations in childhood obesity prevention interventions implemented over the past three decades. Seven meta-analyses and systematic reviews were located for this review or reviews, and from these, 119 unique references were identified. Each article was retrieved and read for appropriateness, and 20 were excluded for a variety of reasons (ex. not published in English language), resulting in 99 articles included for this study. Overall, process evaluations were not well reported upon. Only 38 studies reported the fidelity of program implementation, 25 studies tracked participant attendance, 29 studied evaluated participant satisfaction, and 49 studies reported how staff members were trained. Additionally, one-third of the studies did not report using a single type of process evaluation, and only 5 studies reported using all four types. Results from this study suggest that the use of process evaluations has been low in this area of research, which may explain why many obesity prevention studies have reported mixed or modest results. Suggestions for implementing simple, yet effective process evaluations in future studies will be presented.